Effekte eines Krafttrainings mit explosiv-isometrischen Kontraktionen - Schlumberger, A.; Schmidtbleicher, D. (Deutsche Zeitschrift für Sportmedizin, 2001)
This work evaluates the effects of a strength training program with fast isometric contractions. Nineteen trained physical education students were divided into an experimental group (fast isometric contractions, n=10 [age 23.5 ± 3.04 years, height 178.6 ± 7.22cm, body weight 77.4 ± 5.62kg) and a control group (n=9, age 24.0 ± 2.95 years; height 179.1 ± 6.54cm; body weight 78.8 ± 7.95kg). Fast isometric training was performed two times per week for 6 weeks. In each training session the subjects conducted 3 sets of 3 repetitions two elbow angles (80° and 120°). Within a contraction time of 0.75-1.0 sec force had to be developed in the fastest possible manner. Prior to, after three weeks of training and three days after the last training session rate of force development and maximum strength were measured. Fast isometric training had no significant influence on rate of force development and maximum strength. A detailed analysis of training values showed that the subjects were not able to increase strength values in the course of the six week training period. The reason could be that subjects had difficulties reaching a maximal neural command in the fast isometric contraction task.